Connotation And Clarity Of Meaning In Linguist Speech At Al Mutazilia. A .p Layla Abbas Khamis. (Journal of the College of Basic Education, 2026)
Connotation consider method and feature of Arabic Language features, the meanings mixing with other meanings raise the Linguist speech, and this feature describe the Linguist research at Language scholars, in public and specially at Fund ament alists and Mutazilites of them they get out the Connotation to deep meaning to serve their Fundamentalist beliefs the research depends on Connotation study at Mutazilites and its effect on the clarity of meaning and consolidating the deep meaning treated mentaly proof of fundamentalist belifes which they made the exis of similar verses in the holy Quran we see them bonding between connotation and truth and metaphor in statement of clarity in semantic shift what happens to words and the connotation at Mutazilites it do come for nothing it comes intentionally By the speaker in order to make the words clear in deep meaning in Linguistic Discourse provided that the speaker is knowledgeable about the secrets of Language because the connotation between the speaker and the words and meaning it open connection to raise the Linguist speech level the connotation focuses at Mutazilites on mental evidence in directing the verses of the Quran from the apparent to its deep meaning which has an effect to raise the Linguist speech level to prove that the verses carry adeep meaning that it is clear eloquence and rhetoric the Quran speech which most of the time it must be subject to the authority of reason and logical evidence they have this meaning is subject to the evidence of reason compatible with their beliefs and direct it intentionally in order to know the clarity of deleted deep meaning in Linguist speech.